The progress of microevolution in hybrids of rock lizards of genus Darevskia - F. Danielayn; M. Arakelyan; I. Stepanyan (ՀՀ ԳԱԱ հրատ.)
Along with sterile triploid females, the male hybrids, intersexual individuals, female hybrids with developing follicles and eggs as well as tetraploid male hybrid are found in the mixed population of three species of rock lizards’ genus Darevskia in mountain steppe zone of central Armenia. Intensive microevolution takes place in this sympatric population. The evolutionary potential for hybridogenic speciation by Caucasian rock lizards is discussed. Հայաստանի կենտրոնական մասի լեռնատափաստանային գոտում, Darevskia ցեղին պատկանող երկսեռ և կուսածին ժայռային մողեսների երեք տեսակների խառը պոպուլյացիաներում, ստերիլ տրիպլոիդ էգերի հետ հայտնաբերվել են տրիպլոիդ հիբրիդային էգեր` զարգացող օօցիտներով և ձվերեվ, հիբրիդային արու և ինտերսեքսուալ առանձնյակներ, ինչպես նաև տետրապլոիդ արու առանձնյակ: Այդ պոպուլյացիայում ընթանում է միկրոէվոլյուցիոն գործընթաց: Քննարկվում է Կովկասյան ժայռային մողեսների հիբրիդոգեն տեսակառաջացման էվոլյուցիոն պոտենցիալը: В горно-степной зоне центральной Армении, в смешанной популяции трех видов двуполых и партеногенетических скальных ящериц рода Darevskia, наряду со стерильными триплоидными гибридными самками, обнаружены триплоидные гибридные самки с развивающимися фолликулами и яйцами, гибридные самцы, интерсексуальные особи, а также тетраплоидный гибридный самец. В данной смешанной популяции протекает интенсивный микроэволюционный процесс. Обсуждается эволюционный потенциал гибридогенного видообразования у Кавказских скальных ящериц.
Keywords: Biology; Applied Biology